UNRESOLVED QUESTIONS ABOUT COATS DISEASE: A CASE REPORT: Poster Presentation - Case Report - General practitioner - Ardityastiti, Khairani Azizah; Wibawaty, Halida (Majalah Oftalmologi Indonesia, 2023)
Introduction : Coats disease (CD) is an idiopathic retinal vascular disorder accompanied by retinal telangiectasia with intraretinal and/or subretinal exudation without appreciable retinal or vitreal traction. The disease most common in young males and unilateral involvement. The etiopathogenesis of CD is unclear. However, previous studies have reported changes in inflammatory cytokines, and levels of VEGF in aqueous humor are also higher in patients with CD. Case Illustration : We reported a 19-year-old man with complaints of decreased vision, floaters, and uncomfortable feelings in his RE, since one year before presentation. Initial examination showed visual acuity of the RE was 0.5F2 and the LE was 1.0. Examination of posterior segment showed irregularly-dilated telangiectatic vessels and exudative RD. We performed an OCT examination in both eyes and the results showed extensive cystoid macular edema in the RE. Ultrasonography of the RE also showed an exudative RD. The patient was diagnosed with Coats disease grade 3 and planned to receive intravitreal anti-VEGF injection in RE. After the second injection, OCT examination results showed no improvement in the patient's eye condition. Until now, we’re still trying to find a suitable therapy and considering laser photocoagulation. Discussion : Previous studies showed that there was an improvement in some CD patients only with anti-VEGF injections, but some other patients didn’t improve and had to get other additional therapy with laser photocoagulation/cryotherapy. It’s related to the severity of the disease, where a disease with grade ?3, tends to require combination therapy with laser photocoagulation/cryotherapy. Conclusion : Intravitreal anti-VEGF injections alone don’t show improvement in CD grade?3.